LOCAL ECONOMIC DEVELOPMENT THROUGH TOURISM IN SAMARINDA - Rahman, Muhammad Aditya; Hadi, Saiq Saiful; Putra, Akhmad Fido Ramdhani Elfatian; Fadhilah, Nurul (Fakultas Ekonomi dan Bisnis Islam IAIN Kerinci, 2024)
This study aims to examine the impact of tourist destinations on the social and economic influence of the local community's destination. This method uses qualitative descriptive and purposive sampling methods and focuses on the chairman of the business group. The results of this study indicate a synergy between the existence of the tourism sector to improve the economy and social community in tourist destination areas.